Jak powiedzieć, żeby nie powiedzieć (lub odwrotnie), czyli kłopoty z przekładem elegii wygnańczej Owidiusza „Ex P.” IV 12 - Wesołowska, Elżbieta (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
Aside from its wealth of meaning and contexts, Ovid’s poetry seems to be sometimes difficult to translate into Polish. This paper shows such an extreme situation using the example of Ex P IV 12, where the translator is virtually helpless in the face of the poet’s subtle sense of humor and sophisticated play with a reader on the grounds of the nature of Roman elegiac distich.